Sustainable Three‐Component Synthesis of Isothioureas from Isocyanides, Thiosulfonates, and Amines1. (15th September 2014) - Mampuys, Pieter; Zhu, Yanping; Vlaar, Tjøstil; Ruijter, Eelco; Orru, Romano V. A.; Maes, Bert U. W.
Abstract Multiple applications of isothioureas as fine chemicals (or their precursors) are known, but a general sustainable method for their synthesis was hitherto unavailable. We report a novel general approach towards S‐alkyl and S‐aryl isothioureas through a copper(I)‐catalyzed three‐component reaction between amines, isocyanides, and thiosulfonates. The formal synthesis of a superpotent sweetener further illustrates the applicability of our method.